An extraordinary chlorophyll-a enhancement event jointly induced by two sequential tropical cyclones in the Kuroshio region south of Japan - Zheng, Hui; Zhang, Wen-Zhou (Frontiers in Marine Science, 2023)
We used Biogeochemical-Argo (BGC-Argo) float observation profiles and satellite data to investigate the physical-biogeochemical processes of a phytoplankton biomass rise in the Kuroshio region south of Japan during a period of two sequential tropical cyclones (TCs)-Hagibis and Neoguri-in October 2019. During TC Hagibis, prominent sea surface cooling and surface chlorophyll-a (Chl-a) increase occurred within a pre-existing cyclonic eddy (CE) south of Japan. Because of TCinduced mixing and upwelling, the maximum cooling happened at the depth of 57 m where water temperature dropped by 6℃. The dramatic mixing and upwelling redistributed chlorophyll-a vertically (reducing subsurface Chl-a and increasing surface Chl-a) with little augment of depth-integrated Chl-a in the upper ocean above 160 m depth. Meanwhile, the mixing and upwelling transported nutrients from the subsurface to the surface layer. In the week after Hagibis, the depth-integrated Chl-a greatly increased. Subsequently, TC Neoguri obviously enhanced the augment of phytoplankton biomass although it was weaker than Hagibis. The upwelling induced by Hagibis increased nutrients in the water below 80 m, providing a very favorable condition for the subsequent TC Neoguri to further promote the growth of phytoplankton. The intense precipitation accompanying with Neoguri brought the coastal water with rich terrestrial material to offshore ocean, increasing nutrients and decreasing salinity in the subsurface layer. These both contributed to the marked increase in Chl-a during Neoguri. Our results demonstrated that the two sequential TCs worked together with a cyclonic eddy to cause a drastic and complex Chl-a enhancement event in the Kuroshio region south of Japan.